Philocalic Sol: Love (Be You)-tifully - Visagie, Pejamauro (Open Mic: A Creative Writing Journal, 2024)
I am air. An heir to be… Pollination and legacy, you see. If you are inclined to read between the lines, then you will be all you can, Bee. Be-You... to full-on become, Evermore beautiful.